2002
DOI: 10.1348/000712602162553
|View full text |Cite
|
Sign up to set email alerts
|

Sharing humour and laughter in autism and Down's syndrome

Abstract: Everyday humour and laughter can tell us about children's ability to engage with and understand others. A group of 19 pre-school children with autism and 16 pre-school children with Down's syndrome, matched on non-verbal mental age, participated in a cross-sectional study. Parental reports revealed no group differences in overall frequencies of laughter or laughter at tickling, peekaboo or slapstick. However, in the autism group, reported laughter was rare in response to events such as funny faces or socially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
109
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 39 publications
11
109
1
10
Order By: Relevance
“…However, this was only observed in the younger (5 to 9 years) group. Similarly, Reddy et al (2002) found that children with autism were significantly more likely to produce unshared laughter than healthy control children. Parents of children with autism reported that their children's laughter was common in strange or inexplicable situations but relatively rare in response to events such as funny faces when it would have been expected.…”
Section: Humorous Film Clipsmentioning
confidence: 87%
See 2 more Smart Citations
“…However, this was only observed in the younger (5 to 9 years) group. Similarly, Reddy et al (2002) found that children with autism were significantly more likely to produce unshared laughter than healthy control children. Parents of children with autism reported that their children's laughter was common in strange or inexplicable situations but relatively rare in response to events such as funny faces when it would have been expected.…”
Section: Humorous Film Clipsmentioning
confidence: 87%
“…Brought to you by | Université de Genève -Bibliothèque de Genève Authenticated Download Date | 9/15/17 3:16 PM suggested that individuals with ASD may appreciate more basic types of humor (Reddy et al 2002;Ricks and Wing 1975). The current study clearly indicated that children with AS enjoy humorous material as much as healthy children do, if the humor elements are simple and the incongruence can be perceived independently from theory of mind requirements, inferential demands, or language abilities, as was the case in the slapstick scenes of the present study.…”
Section: Humorous Film Clipsmentioning
confidence: 99%
See 1 more Smart Citation
“…St. James and Tager-Flusberg (1994) showed that children with autism can produce and appreciate humor to a limited extent in naturalistic settings: no differences were found in earlier forms of humor (e.g., humor based on rhyme, slapstick, funny sounds) but in nonverbal incongruity and riddles (children with autism produced no riddles at all). Another study showed children with autism laugh as much as children with Down's syndrome in response to tickling and slapstick humor, but exhibit less laughter in response to socially inappropriate acts (Reddy et al 2002). In a more experimental setting, two studies showed that comprehension of humorous material is poorer in individuals with AS or autism than controls (Ozonoff and Miller 1996;Emerich et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the stimuli and tasks used in previous studies might have lead to different conclusions: Generally, it is assumed that those individuals with AS and autism who have highly developed linguistic and computational abilities approach humor from a more cognitive/intellectual perspective and are able to grasp the cognitive basis of humor (e.g., such as recognizing violations of linguistic and logical principles; for a review, see Lyons and Fitzgerald 2004). However, the underlying mechanisms for the impairments, particularly in more complex forms of humor, are controversially discussed: for example, St. James and Tager-Flusberg (1994) assumed that the reduced humor processing skills derive from difficulties in social-cognitive deficits in understanding mental states (see also Baron-Cohen et al 1993), whereas Reddy et al (2002) assumed that difficulties in mutual attention and emotion sharing cause these effects rather than symbolic and meta-representational skills. Emerich et al (2003) claimed that deficits in humor processing arise due to impairments in cognitive flexibility and coherence building, as these skills are necessary in order to reinterpret the meaning of parts of the joke.…”
Section: Introductionmentioning
confidence: 99%